China’s marine plastic pollution governance path: focusing on the judicial positioning of PIL initiated by procuratorial agencies - Ben-Chao Fu; Chuan-Kai Guo; Xiu-Juan Li; Hai-Dong Cai; Jin-Hua Guo; He-Ran Li (Frontiers in Marine Science, 2025)
Can procuratorial agencies play a key role in China’s governance of marine plastic pollution (MPPG)? Within the current discussions about the legal framework of China’s MPPG, courts, marine environmental regulatory authorities, procuratorial agencies, and environmental protection organizations are typically seen as the main stakeholders. However, the role of procuratorial agencies, as the statutory entity for initiating PIL in marine environmental protection, has been significantly overlooked. This raises a range of questions including how should procuratorial agencies leverage their advantages in PIL to enhance the diversity of participants in the litigation process? What inherent challenges exist in marine environmental lawsuits? What substantive and procedural obstacles will procuratorial agencies face when engaging in MPPG-related litigation? This study argues that procuratorial agencies, by fulfilling their public interest litigation (PIL) function in marine environmental protection, can effectively improve MPPG governance. The study focuses on issues such as the unclear prerequisites for initiating MPPG-related lawsuits by procuratorial agencies, the criteria for selecting diverse litigation models, and the applicability of procuratorial agencies’ PIL in foreign-related cases.